4 (literary) portraits of teachers by 4 portrait masters (Journal of Parents and Teachers, 2014)
A classroom activity is presented. It consists of portraying the teachers in a humanistic way. In this article there are 4 examples of portraits of teachers, all written by students. These portraits are accompanied by questions and descriptions of elements that can be observed in the texts, or elements that are simply relevant. At the end of the article, a small index about the three-dimensional profile of a character has been included, which can help students who are going to write a "portrait".
Keywords: Portrait; narrative; students; teachers; description; activity; classroom